Highly Thermally Conductive Yet Flexible Composite of Carbon Fiber, Carbon Nanotube, and Rubber Obtained by Decreasing the Thermal Resistivity at the Interface between Carbon Fiber and Carbon Nanotube1 . Issue 2 (2nd November 2016) - Ata, Seisuke; Subramaniam, Chandramouli; Nishizawa, Ayumi; Yamada, Takeo; Hata, Kenji
Abstract : Thermal management of personal computer and other devices are critical issue for stable operation. Especially, soft and high thermal conductive materials are widely required for thermal transfer from heat source to heat sink. In this study, we prepared high thermal conductive composite with long single wall carbon nanotube, pitch‐derived carbon fiber and fluorinated rubber. Thermal conductivity of the composites is up to 80 W mK −1 which is higher than that of iron or brass. Furthermore, origin of the high thermal conductivity of the composites is investigated by using Weidman–Franz low. Carbon nanotubes enhance phonon thermal transfer between carbon fiber to carbon fiber. Abstract : A flexible and high thermal conductive rubbery sheet is achieved by mixing supergrowth single wall carbon nanotube, pitch‐based carbon fiber, and fluorinated rubber. The hybrid thermal conductive sheet shows more than 80 W mK–1 which is higher than that of brass. This composite is promising material for thermal interface material (TIM).